2011
DOI: 10.2135/cropsci2010.12.0700
|View full text |Cite
|
Sign up to set email alerts
|

When Does Hard Coat Impose Dormancy in Legume Seeds? Lotus and Scorpiurus Case Study

Abstract: In many legumes, the germination ability of newly harvested seeds is controlled by fwo contrasting processes, fhe maturation process and fhe esfablishmenf of seed coat dormancy, which prevents fhe germinafIon of mature seeds. These two processes are offen sfaggered, so that seeds may achieve a transifory ability fo germinafe long before fhe esfablishmenf of seed coaf dormancy. To clarify fhese issues, a field and laborafory experimenf was conducted on fwo Mediterranean legume species, Lotus ornithopodioides L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…In our study, even seeds from fresh GF pods were readily able to germinate, as non-dormant, while PY established between the two latest maturity stages (i.e., BH and BD pods), when pod color had already changed to brown and a steep seed mass decrease had occurred. These findings are consistent with those obtained in other pasture Mediterranean legumes [ 11 , 18 , 53 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, even seeds from fresh GF pods were readily able to germinate, as non-dormant, while PY established between the two latest maturity stages (i.e., BH and BD pods), when pod color had already changed to brown and a steep seed mass decrease had occurred. These findings are consistent with those obtained in other pasture Mediterranean legumes [ 11 , 18 , 53 ].…”
Section: Discussionsupporting
confidence: 93%
“…For this reason, seed dormancy and germination patterns in legume species have been long since investigated, mainly in wild annual taxa (e.g., Lotus , Trifolium , Medicago, and Scorpiurus ) [ 9 , 10 , 11 , 12 ]. Annual legumes have an elevated capacity of self-reseeding, but also low levels of germinability [ 13 ], a trait that was found to be linked to a strong PY mechanism, preventing seeds from achieving rapid germination, optimal emergence and uniform seedling establishment [ 6 , 8 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to assess germination speed, the counts of germinated seeds were used to estimate non-parametric germination curves, by utilizing the Kaplan-Meier (KM) method, as implemented in the 'Survfit' function in R [63]. The KM method belongs to the body of survival analyses, and it has been successfully used to model seed germination [64,65] because it enables the expression of the proportion of seeds germinated/seedlings emerged as a function of time without reference to any predetermined equation. KM curves were used to derive the time for 10%, 30% and 50% germination, whose reciprocals were taken as the germination rates (GRs, in 1/d) for the corresponding percentile (GR 10 , GR 30 and GR 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies on seed development have shown that the transition from a permeable to impermeable seed coat coincides with the decline in moisture content during the maturation drying phase of seed development (Jaganathan 2016). Indeed, it has been observed in a few species that the seed coat becomes impermeable only when the moisture content of the seeds falls to a specifi c threshold level (Hyde 1954;Gladstones 1958;Egley 1979;Chinnasamy & Bal 2003;Hay et al 2010;Gama-Arachchige et al 2011;Gresta et al 2011). Th us, the number of seeds with impermeable seed coats produced by plants may vary between sites or within years based on the moisture content reached during maturation drying, which is aff ected by the environmental conditions including temperature and relative humidity.…”
Section: Introductionmentioning
confidence: 99%